Islam and Local Culture: Shifthing Values of Religious Practices Among Modern Javanese Society - Wibowo, Arif (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This paper aims to explore more deeply the clustering of society in the understanding of Islam. Clifford Geertz's clustering or classification of society in his previous research, as an initial reference to look at the development of the era until now. This clustering, if seen carefully, is still strongly felt in modern society today. So the author tries to detect back from previous research to the symptoms that occur today. This research uses the Systematic Literature Review (SLR) method. The main literature is Clifford Geertz's research in his book The Religion of Java. By reviewing the book, the author found a clustering or classification of people in East Java about the understanding of Islam divided into 3 (three), namely: (1). the abangan, (2). the santri, and (3). the priyayi. By looking at the clustering of society according to Clifford Geertz's perspective, which is then used as a basic theory to look at modern society today, it turns out that there is still no change. In society, this clustering is still felt indirectly. There is still a group that is the object of preaching as the abangan, there is a group of santri as preachers and also the priyayi or officials. Which starts from the seat will be made different, both quality and position. Then from there are certain areas that can only be accessed by certain groups. Based on this theory, we can also observe shifts in the social and spiritual values of modern Javanese society. Specifically, regarding the traditions of slametan, religious study circles, and mosques, which have been central to Javanese society since ancient times. There have been several shifts in the values of the slametan tradition, namely a shift from communal-symbolic values to functional-practical values. The symbolic meaning of culture has begun to fade. In the general pengajian tradition, as a means of religious education, there has been a shift from face-to-face, charismatic values to digital, informative values. The style of religious communication has become more informal, audiovisual, and entertaining. Mosques, as social-spiritual centres, have shifted from being collective social-spiritual centres to formal spiritual symbols. Young people are beginning to distance themselves from physical religious activities.